Hand hygiene: a review of understanding and attitudes of healthcare professionals - Jéssica Raunne Moreira de Sousa; Luiz Felipe Duarte dos Santos; Ana Amélia de Carvalho Melo Cavalcante; Maria do Carmo Mascarenhas; Tatiana Vieira Souza Chaves; Tereza Maria Alcântara Neves (Universidade Federal do Estado do Rio de Janeiro, 2014)
Objective: Evaluate hand hygiene performed by health professionals in a public hospital and identify non-adherence factors for the correct technique. Methods: The professionals were submitted to a questionnaire, testing their knowledge of Hand Hygiene Compliance for Health Professionals and were observed while hand washing. Results: 62.5% received training either during undergraduation course, or by the hospital, while 37.5% did not know how to do the technique. Regarding the reason for the noncompliance of proper hygiene techniques, 61.1% of professionals said that excessive professional activity, and insufficient time are the main causes. 44.4% mentioned the lack of priority of the institution as to the procedure and 16.6% lack the time to perform the technique. Conclusion: It appears that most of the professionals interviewed did not obey the rules recommended hand hygiene and the main reason is no time due to excessive workload. Descriptors: Infection, Hand hygiene, health professionals.